Post-conflict nutritional status of school-age children in North Wollo zone, Northeast Ethiopia: a multi-center cross-sectional study - Zelalem Dejazmach; Birtukan Gizachew Ayal; Woldeteklehaymanot Kassahun; Getinet Kumie; Muluemebet Kassa; Berihun Mulu Yayeh; Seada Seid Ahmed; Abebe Worku Gela; Habtu Debash; Selamawit Ayalew; Asmamaw Ameshe; Abebaw Alamrew; et al. (BMC Public Health)
Abstract Background Conflict invariably disrupts food production in affected areas, exacerbates food insecurity, and results in population displacement. In 2021, the invasion of the Amhara region by the Tigrayan armed group led to widespread impoverishment of much of Amhara population. The conflict particularly exacerbated malnutrition rates in the North Wollo Zone. Despite this, studies focusing on undernutrition in conflict-affected areas within the Zone have not yet been documented. Therefore, this study assessed post-conflict nutritional status of school-age children in Northeast Ethiopia. Methods Cross-sectional study was conducted from April to May 2022 within the community, involving 584 school-age children. Socio-demographic data was collected through a structured questionnaire, and anthropometric measurements were transformed into indices using the World Health Organization’s Anthro-software. Descriptive and analytical statistical analyses were conducted with a 95% confidence interval. A p-value of less than 0.05 was regarded as statistically significant in the multivariate regression models. Results Among the 584 participants, 45.7% (95% CI: 42.0–50.0) were found to be stunted, while 33.0% (95% CI: 29.3–37.0) were classified as thin. Stunting was significantly associated with being: age 10–14 years (AOR = 6.16, 95% CI: 3.89–9.78); male (AOR = 1.52, 95% CI: 1.03–2.22); having an employed father (AOR = 3.40, 95% CI: 1.46–7.92); having farmer father (AOR = 4.70, 95% CI: 2.61–8.47). The odds of thinness were significantly higher among children who were male (AOR = 1.93, 95% CI: 1.23–3.03); lived in rural areas (AOR = 2.84, 95% CI: 1.55–5.20); had a mother who was a housewife (AOR = 4.38, 95% CI: 2.09–9.18) or a merchant (AOR = 4.84, 95% CI: 1.72–13.61); had a merchant father (AOR = 14.06, 95% CI: 6.97–28.35) or employed (AOR = 11.41, 95% CI: 4.33–30.07); and lived in a food-insecure household (AOR = 6.17, 95% CI: 3.84–9.90). Conclusions Undernutrition is significant public health concern among school-age children in the conflict-affected study area. Stunting and thinness were significantly linked to factors such as the child’s sex, age, parents’ occupational status. These findings underscore the pressing need to implement health and nutrition programs aimed at enhancing the nutritional status of school-age children in the conflict-affected region.